Facet-resolved electrochemistry: From single particles to macroscopic crystals - Zhang, Song; Ciampi, Simone (ELSEVIER, 2022)
Optimizing the kinetics and energy requirements of electrochemical reactions is central to the design of redox systems whose function ranges from energy conversion, to chemical catalysis and sensing. This optimization takes often the form of a trial-and-error search for the optimal electrode material. Recent research has revealed pronounced facet-dependent electrical conductivity, redox reactivity and electro-adsorption for a range of technologically relevant semiconductors, including silicon, Cu2O, GaAs, InN, Ag2O, and β-Ga2O3. We analyze selected recent reports, highlighting situations where testing alternative crystal cuts of the same material can be an effective electrode-optimization process. We discuss what is unambiguously known as well as what is emerging but still unclear, such as when and how electrical conductivity and electrochemical rates scale with each other (and when not), or the use of facet-dependent electro-adsorption to direct crystal growth and monolayer deposition. When there are contrasting or counterintuitive views, we explore the assumptions that underlie them.